Temperate deciduous shrub and tree In situ autumn phenology 2017, 2018, 2020, 2021. Downer Woods, Milwaukee, Wisconsin, USA - Alison Donnelly (PANGAEA, 2024)
This data set includes in situ observations (Day of year) of a range of spring (budburst, leaf-out and full leaf unfolded) and autumn (leaf color and leaf fall) phenology (2017-2021) of a range of co-occurring species of tree (Fraxinus spp. (ash), Tilia americana (American-basswood), Quercus rubra (red-oak), Quercus alba (white-oak) and Acer negundo (boxelder)) and shrub (Native species: Prunus virginiana (chokecherry), Cornus alternifolia (pagoda-dogwood), Viburnum lentago (nannyberry), Ribes americanum (American-wild-currant) and Euonymus atropurpureus (Eastern wahoo) and Non-native species: Rhamnus cathartica (buckthorn), Lonicera morrowii (honeysuckle), Ligustrum vulgare (European-privet) and Viburnum opulus (European-highbush-cranberry)) in an urban woodland fragment in Wisconsin, USA. Spring data span 2017, 2018, 2020 and 2021 whereas autumn data span 2018-2021. The reason data for spring 2019 are omitted is due to observer error which resulted in a number of inconsistencies so the entire season has been omitted.